1988
DOI: 10.1002/mus.880110110
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time ultrasound imaging of muscles

Abstract: A prospective study was done on 222 consecutive new patients referred to our pediatric muscle clinic to assess the diagnostic value of ultrasound imaging. Ultrasound scans were interpreted without knowledge of clinical presentation or results of other tests. Muscular dystrophy produced a brightly speckled pattern of increased echo from the muscle, whereas spinal muscular atrophy showed a moderate increase in muscle echo and associated muscle atrophy. Acute dermatomyositis produced a moderate increase in echo t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
1
3

Year Published

1991
1991
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(113 citation statements)
references
References 10 publications
7
100
1
3
Order By: Relevance
“…2B). Similar findings were also observed in other involved muscles, in dicating an invasion of the muscles by collagen fibers or adipose cells [7], Muscle biopsy from the left quadriceps femoris showed that almost all the muscle fibers had central nuclei with mild variation in fiber size: a small number of fibers had normal diameters ranging from 60 to 80 pm, but the majority of fibers were of a small caliber (less than 40 pm) ( fig. 2C).…”
Section: Case Reportsupporting
confidence: 61%
“…2B). Similar findings were also observed in other involved muscles, in dicating an invasion of the muscles by collagen fibers or adipose cells [7], Muscle biopsy from the left quadriceps femoris showed that almost all the muscle fibers had central nuclei with mild variation in fiber size: a small number of fibers had normal diameters ranging from 60 to 80 pm, but the majority of fibers were of a small caliber (less than 40 pm) ( fig. 2C).…”
Section: Case Reportsupporting
confidence: 61%
“…10 -14 In particular, patients with neuromuscular disorders have elevated muscle echo intensity levels caused by infiltration of muscle architecture by fat and connective tissue. 15 Through methods of quantification of muscle echo intensity, QMU can serve as a biomarker for SMA severity. 16 In this study, ultrasound measurements were taken on the Terason 2000 Handheld Ultrasound System (Terason, Burlington, MA), and analysis was performed on the transverse images that were exported to Adobe Photoshop.…”
Section: Subjectsmentioning
confidence: 99%
“…Più la fibrosi risulta accentuata, maggiore risulta l'impedenza acustica del fascio ultrasonoro in profondità e l'attenuazione della progressione del fascio ultrasonoro rende sempre più difficile il riconoscimento del margine osseo sottostante. Pertanto, il grado di sovvertimento ecostrutturale è in relazione con la gravità del quadro clinico [16,1719,20,21,38,57]. Per una recente rassegna di interesse pediatrico si veda Pillen et al [42].…”
Section: Fig 7 Aspetto Clinico Del Muscolo Tibiale Anteriore Destro (unclassified